Spoken Language Skills in Children With Bilateral Hearing Aids or Bilateral Cochlear Implants at the Age of Three Years - Välimaa Taina T; Kunnari Sari; Aarnisalo Antti A; Dietz Aarno; Hyvärinen Antti; Laitakari Jaakko; Mykkänen Sari; Rimmanen Satu; Salonen Jaakko; Sivonen Ville; Tennilä Tanja; Tsupari Teija; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objectives:
Early hearing aid (HA) fitting and cochlear implants (CIs) aim to reduce the effects of hearing loss (HL) on spoken language development. The goals of this study were (1) to examine spoken language skills of children with bilateral HAs and children with bilateral CIs; (2) to compare their language skills to the age-norms of peers with normal hearing (NH); and (3) to investigate factors associated with spoken language outcomes.
Design:
Spoken language results of 56 Finnish children with HL were obtained from a nationwide prospective multicenter study. Children with HL comprised two groups: children with mild-to-severe HL who used bilateral HAs (BiHA group, n = 28) and children with profound HL who used bilateral CIs (BiCI group, n = 28). Children's spoken language comprehension, expressive and receptive vocabulary, and phonological skills were compared with normative values of children with NH at the age of three years. Odds ratio (OR) was calculated to compare proportions of children below age-norms in BiHA and BiCI groups. Factors associated with spoken language outcomes were modeled with analysis of covariance.
Results:
At the age of 3 years, 50%-96% of children with HL performed 1 SD or more below the mean of the normative sample of age-peers with NH in spoken language skills, depending on the language domain. Receptive vocabulary and phonological skills were the most vulnerable language domains. In receptive vocabulary, 82% of the children in the BiHA group and 50% of the children in the BiCI group scored 1 SD or more below the normative mean. The BiHA group was 4.4 times more likely to have poorer receptive vocabulary than the BiCI group. In phonological skills, 96% of children in the BiHA group and 60% of the children in the BiCI group scored 1 SD or more below the normative mean. The BiHA group was 18.0 times more likely to have poorer phonological skills than the BiCI group. The analysis of covariance models showed that unaided pure-tone average, PTA(0.5-4 kHz), had a significant effect on spoken language comprehension in the BiHA group. For the BiCI group, age at HL diagnosis and age at CI activation had a significant effect on expressive vocabulary. High maternal level of education had a significant effect on language comprehension and expressive vocabulary and female gender on phonological skills.
Conclusions:
At the age of 3 years, especially receptive vocabulary and phonological skills caused difficulties for children with HL showing also considerable individual variation. Children with bilateral HAs seemed to be more likely to have poorer receptive vocabulary and phonological skills than children with bilateral CIs. A variety of factors was associated with outcomes in both groups. Close monitoring of spoken language skills of children with HL is important for ensuring similar opportunities for all children with HL and timely intervention, when needed.